2020
DOI: 10.1007/s00268-020-05644-6
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ to Midterm Results After Posterior Component Separation with Transversus Abdominis Release: Initial Experience from India

Abstract: Purpose Posterior component separation with transversus abdominis release is a new procedure and is quickly gaining popularity. It has shown promising results in terms of low recurrence rates for large and complex hernias. However, there are very little Indian data available on this to date. The purpose of this study was to assess the outcomes of the technique at three centers in India. Methods This was a retrospective analysis of the prospectively collected data. Patients with a minimum follow‐up of 3 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
3
6
1
Order By: Relevance
“…Despite these advantages, operative times for R-TAR are longer than for open TAR [27,29]. It has been reported in the literature that the operative times for the open TAR technique range from 188 minutes to 383 minutes [14,20,[30][31][32][33][34]. The mean operative time in the present study was 248 minutes, which is comparable to the aforementioned studies.…”
Section: Discussionsupporting
confidence: 77%
“…Despite these advantages, operative times for R-TAR are longer than for open TAR [27,29]. It has been reported in the literature that the operative times for the open TAR technique range from 188 minutes to 383 minutes [14,20,[30][31][32][33][34]. The mean operative time in the present study was 248 minutes, which is comparable to the aforementioned studies.…”
Section: Discussionsupporting
confidence: 77%
“…Wound complications reported in comparable studies (SSO 3-39%, SSE 3-14%, SSOPI 3-12%) resemble the results reported here, except for SSE (23%), which was high in the first episode (8,11,13,15,18,20,(45)(46)(47)(48)(49). While SSE is underreported in most studies, and no specific cause can be designated, this may be related to the TAR learning curve (8,13,15,48,49). The rate of patients without any systemic complication cannot be deduced in any other study, nor can it be adequately compared with our results.…”
Section: Evaluation Of Outcomessupporting
confidence: 86%
“…Latest alteration in component separation techniques is the transversus abdominis release (TAR) (8)(9)(10)(11)(12)(13)(14)(15). This posterior CST was introduced in 2012 as an alternative to the classic anterior component separation technique (Ramirez) (8,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed open TAR, in studies which mentioned both open and robotic data [12,21,24,25,27], we included their data for open TAR in the analysis. The recent meta-analysis comparing outcomes of open vs robotic TAR [35], concluded that though overall complications and SSO rates are low in robotic TAR, the SSOPI, SSI, reoperation and readmission rates are similar.…”
Section: Discussionmentioning
confidence: 99%